Jagged little pill you live, you learn : the stories behind the iconic album and groundbreaking musical - Morissette, Alanis 1974- (Grand Central Publishing, 2020)
Go behind the scenes with photography, original interviews with the cast, crew, Alanis Morissette, and Diablo Cody, and an introduction from Morissette herself on the album's genesis and journey from release to musical--including details and anecdotes on her collaboration on the show. Including the full annotated libretto and a retrospective look at Alanis's artistic influences and the significance of the album within the cultural context of the 90s as well as its long-term impact on the music world as we know it
Keywords: Morissette, Alanis -- 1974-; Geschichte 1995; Geschichte 2018; Musikalbum; Musical; Morissette, Alanis / Jagged little pill (Musical); American drama / History and criticism; Musicals / History and criticism; Musicals / Production and direction; Musicals / Pictorial works; Musicals / Librettos; American drama; Musicals; Anecdotes; Criticism, interpretation, etc; Interviews; Librettos; Music criticism and reviews; Pictorial works; Theater reviews; Bildband